THE DIALECTICS OF RATIONAL AND EXISTENTIAL ANALYSIS OF SOCIAL AUTOPOIESIS - Pavlovich Pavlov, Alexander; Petrovich Yatsenko, Mikhail; Viktorovna Koreneva, Vera; Georgievna Sinkovskaya, Irina; Gennadyevna Korol, Liudmila; Vladimirovich Rakhinsky, Dmitry (Revista Inclusiones, 2020)
The article is devoted to the phenomenon of social order involving the dialectic unity of existential and societal conditions of social reproduction. The methodological and epistemological base of the study is formed by the theory of autopoiesis by N. Luhmann and ideas of M. Bakhtin, P. Berger, T. Luckmann, E. Terikian, etc. The key issue is what allows for social order and its reproduction (autopoiesis). This problem is examined from the point of fundamental ontology and existential philosophy. The main idea of the article is related to social order being examined as the process of social reproduction (autopoiesis). Social reproduction is not reduced to the reproduction of society and individuals but presents the unity of both. The article also examines the phenomenon of rational society and its main component – “the picture of the world” (symbolic universum). The authors highlight the fact that a new type of autopoiesis adapted for the network conditions of social life is forming in the modern world. The specific feature of this type of autopoiesis is that social reproduction takes place in the conditions of the lack of pictures of the world that have become obsolete as historical phenomena. The fundamental element of social reproduction (autopoiesis) is the social actor that belongs to two worlds: the societal rational world (the world of the System) and the existential world (the world of existence). The article includes the analysis of these worlds and their interrelation and synthesis that allows for the reproduction of social actors.